2017
DOI: 10.3390/met7070278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyrite on Thiosulfate Leaching of Gold and the Role of Ammonium Alcohol Polyvinyl Phosphate (AAPP)

Abstract: Abstract:The effect of pyrite and the role of ammonium alcohol polyvinyl phosphate (AAPP) during gold leaching in ammoniacal thiosulfate solutions were investigated using pure gold foils. The results showed that pyrite catalyzed the decomposition and also significantly increased the consumption of thiosulfate. This detrimental effect became more severe with increasing pyrite content. Further, the presence of pyrite also substantially slowed the gold leaching kinetics and reduced the overall gold dissolution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…They also suggested that ion-exchange resin adsorption may be beneficial for the recovery of aurothiosulphate because resins are often used in pulp or leach and can be easily regenerated. Liu et al [2] investigated the behavior of thiosulfate consumption with pyrite and ammonium alcohol polyvinyl phosphate (AAPP). It has been found that pyrite has detrimental effects on the thiosulfate consumption but AAPP reduces this consumption.…”
Section: Selective Extraction Of Valuable Metals From Wastsmentioning
confidence: 99%
“…They also suggested that ion-exchange resin adsorption may be beneficial for the recovery of aurothiosulphate because resins are often used in pulp or leach and can be easily regenerated. Liu et al [2] investigated the behavior of thiosulfate consumption with pyrite and ammonium alcohol polyvinyl phosphate (AAPP). It has been found that pyrite has detrimental effects on the thiosulfate consumption but AAPP reduces this consumption.…”
Section: Selective Extraction Of Valuable Metals From Wastsmentioning
confidence: 99%
“…In nature, significant amounts of gold are often found in arsenopyrite (FeAsS) [1][2][3]. However, most gold in the arsenopyrite is difficult to leach, mainly because the gold tends to be encapsulated in the mineral matrix [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrite (FeS 2 ) is one of the most common and widely distributed sulphide minerals [1]. In industry, pyrite is a chief raw material to produce sulphur, sulphur dioxide and sulphuric acid.…”
Section: Introductionmentioning
confidence: 99%